ANALYSIS OF THE FUNCTIONAL INCAPACITIES IN THE MULTIPLE SCLEROSIS: REVIEW OF LITERATURE. (Fiep Bulletin - online, 2015)
The Multiple Sclerosis (MS) is a demyelinating ilness that presents as a main characteristic the lesion of the formed myelin and where the injuries are developed in association with perivascular inflammation. The ilness is clinically manifested through a topographical variety of signs and recurrent neurological symptoms, characterizing the dissemination in time and space. The motor damage is one of the most frequent symptoms affecting, consequently, the mobility of the patient. Mobility is a basic part of the preservation of independence and an essential determining of independence and important contribution to disability. Currently, an extensively accepted practice is the use of instruments (scales) to measure the effectiveness of the clinical interventions. Measuring these results become an important factor for the health care previsions helping the patient's quality of life. It's still a reason of discussion in literature which scale has greater reliability and uniformity of results among the examiners. However, these instruments must be reliable since they can be used to change behaviors or to detect characteristics of the clinical evolution of the patient.
Keywords: Multiple Sclerosis; Physiotherapy; Scales.